2004
DOI: 10.1038/sj.ejcn.1601767
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking during pregnancy in rural Nepal. Risk factors and effects of β-carotene and vitamin A supplementation

Abstract: Objective: We examined risk factors of smoking and the association between smoking and pregnancy-related and 6-month infant mortality in rural Nepal, where 30% women reported smoking during pregnancy. Design: Cross-sectional analysis of risk factors associated with smoking status and health consequences of smoking, using prospective data collected as part of a randomized community trial to examine the effect of maternal vitamin A or b-carotene supplementation on maternal mortality. Setting: Rural, southeastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
1
16
1
Order By: Relevance
“…as the birth order increases [26]. Smoking rate was significantly lower in comparison to findings of other studies done in Nepal [1,[27][28][29][30].…”
Section: In Third Trimester (N=226)contrasting
confidence: 54%
See 1 more Smart Citation
“…as the birth order increases [26]. Smoking rate was significantly lower in comparison to findings of other studies done in Nepal [1,[27][28][29][30].…”
Section: In Third Trimester (N=226)contrasting
confidence: 54%
“…This was higher than the rate of alcohol consumption among Nepalese women in Eastern Nepal [27,[29][30].…”
Section: In Third Trimester (N=226)mentioning
confidence: 65%
“…The sample size was calculated based on the assumption that prevalence of tobacco use during pregnancy was 30% (17). The population living in 33 Village Development Committee (VDC) was considered to represent rural population while population living in the only municipality of the district was considered to represent urban population.…”
Section: Methodsmentioning
confidence: 99%
“…The 24-week infant mortality rate in this area was 70.8 per 1000 live births (Katz et al, 2000), more than 10 times higher than that in the developed world. Katz et al (2003) pointed out that maternal undernutrition during pregnancy was strongly associated with infant mortality and Christian et al (2004) revealed potential effects of intervention by means of supplementation of micronutrients on improvement of maternal and infant health and survival. Nutritional status of women is worse in the Terai than in other areas of Nepal.…”
Section: Introductionmentioning
confidence: 99%